Association of Peripheral Blood Cell Profile With Alzheimer's Disease: A Meta-Analysis - Huang, Le-Tian; Zhang, Cheng-Pu; Wang, Yi-Bing; Wang, Jia-He (Frontiers in Aging Neuroscience, 2022)
Background: Inflammation and immune dysfunction play significant roles in the pathogenesis of Alzheimer's disease (AD)-related dementia. Changes in peripheral blood cell profiles are a common manifestation of inflammation and immune dysfunction and have been reported in patients with AD or mild cognitive impairment (MCI). We systematically evaluated the association of peripheral blood cell counts and indices with AD or MCI through a meta-analysis. Methods: We electronically searched sources to identify all case‒control trials comparing peripheral blood cell counts and/or lymphocyte subsets between patients with AD or MCI and healthy controls (HCs). Meta-analyses were used to estimate the between-group standardized mean difference (SMD) and 95% confidence interval (CI). Results: A total of 36 studies involving 2,339 AD patients, 608 MCI patients, and 8,352 HCs were included. AD patients had significantly decreased lymphocyte counts (SMD  -0.345, 95% CI [-0.545, -0.146], P = 0.001) and significantly increased leukocyte counts (0.140 [0.039, 0.241], P = 0.006), neutrophil counts (0.309 [0.185, 0.434], P = 0.01), and neutrophil‒lymphocyte ratio (NLR) (0.644 [0.310, 0.978], P < 0.001) compared to HCs. Similarly, significantly increased leukocyte counts (0.392 [0.206, 0.579], P < 0.001), NLR (0.579 [0.310, 0.847], P < 0.001), and neutrophil counts (0.248 [0.121, 0.376], P < 0.001) were found in MCI patients compared with HCs. A significantly decreased percentage of B lymphocytes (-1.511 [-2.775, -0.248], P = 0.019) and CD8+ T cells (-0.760 [-1.460, -0.061], P = 0.033) and a significantly increased CD4/CD8 ratio (0.615 [0.074, 1.156], P = 0.026) were observed in AD patients compared to HCs. Furthermore, significant changes in hemoglobin level and platelet distribution width were found in patients with AD or MCI compared with HCs. However, no significant difference was found between AD or MCI patients and HCs in latelet counts, mean corpuscular volume, red cell distribution width, mean platelet volume, and CD4+ T, CD3+ T, or natural killer cell counts. Conclusion: Changes in peripheral blood cell profiles, particularly involving leukocyte, lymphocyte, neutrophil, and CD8+ T cell counts, as well as the NLR and the CD4/CD8 ratio, are closely associated with AD. The diagnostic relevance of these profiles should be investigated in future.